Hieratic, Demotic and Greek studies and text editions : of making many books there is no end : Festschrift in honour of Sven P. Vleeming - Donker van Heel, K. (Koenraad); Hoogendijk, F. A. J.; Martin, Cary J. (Papyrologica Lugduno-Batava, 2018)
This volume is a Festschrift in honour of Sven Vleeming containing the contributions of thirty-eight friends and colleagues, often renowned specialists in their respective fields. It includes the editions of fifty-four new texts from Ancient Egypt that date from the 7th century BCE to the 2nd century CE and covers a very wide range of subjects in (Abnormal) Hieratic, Demotic and Greek papyrology. As such, it reflects the equally wide range of knowledge of the scholar to whom this book is dedicated.